Genetically Predicted Circulating Level of C-Reactive Protein Is Not Associated With Prostate Cancer Risk - He, Chiyu; Qian, Yu; Liu, Bin; Yang, Shaoxue; Ye, Ding; Sun, Xiaohui; Chen, Tianhui; Mao, Yingying (Frontiers in Oncology, 2020)
Background: Inconsistent findings from observational studies have reported that C-reactive protein (CRP) is likely associated with risk of prostate cancer. Because conventional observational studies are susceptible to confounding and reverse causality, it remains unclear whether there is a causal relationship of CRP with risk of prostate cancer. Methods: In this study, we applied a two-sample Mendelian randomization (MR) approach to evaluate the potential causal association of circulating CRP levels with prostate cancer risk. Instrumental variables and corresponding genetic association estimates for circulating CRP levels were obtained from a meta-analysis of genome-wide association studies (GWASs) including 204,402 participants of European descent. The genetic association estimates of these instrumental variables with prostate cancer were obtained from a GWAS meta-analysis including 79,148 cases and 61,106 controls of European ancestry. The inverse-variance weighted (IVW) method was used as primary MR analyses, while in sensitivity analyses, MR-Egger regression and MR pleiotropy residual sum and outlier (MR-PRESSO) test were used to assess the presence of pleiotropy. Odd ratio (OR) and 95% confidence interval (CI) were calculated. Results: Overall, 58 single nucleotide polymorphisms (SNPs) were used as instruments for circulating CRP levels. MR analysis suggested that genetically determined CRP levels were not associated with prostate cancer risk (OR=1.06, 95% CI= 0.96-1.16) using the IVW method. Sensitivity analyses using alternative MR methods produced similar results (OR = 1.00, 95% CI = 0.93-1.08 for the weighted-median method; and OR = 1.02, 95% CI = 0.95-1.08 for MR-PRESSO test). MR-Egger regression did not suggest evidence of directional pleiotropy (P=0.25). Conclusions: Our study found that genetically predicted circulating CRP levels were not associated with prostate cancer risk, suggesting that CRP is unlikely to be a causal factor in the development of prostate cancer.